CONGKLAK GAMES TO REDUCE THE SHAKING HEAD BEHAVIOUR IN CHILDREN WITH AUTISM X GRADE 4C IN SLB LUBUK KILANGAN PADANG - Riri Kasmia (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrack: This study originated from the observation that researcher found when making observations. The researcher found a child with autism who experience barriers to behavior like shaking his head. From the observations, the  researcher found child likes shook his head, shaking his head carried by the child prior to the learning process that is 15 times at 7:30 a.m. to 08:00 and  22 times at 08:00 to 9:30 a.m during the learning process and 21 times at 10:00 to 12:00 a.m . the purpose of thyis study aims to prove the effectiveness of the congklak game to reduce head shaking behavior in children with autism grade 4C SLB Lubuk Kilangan Padang. This study uses a single case experimental approach in the form of a multiple baseline design, using a multiple baseline design cross conditions. The results of the study on baseline conditions (A) behavior of children shaking head varies the condition before entering (07:30 to 08:00 a.m) in the range of 10-18 times, the condition before the break (8:00 to 9:30 a.m) in the range of 7-23 times and condition after the break (10:00 to 12:00) in the range of 12-21 times. In the intervention condition (B) in the form of game congklak the result that children head shaking behavior experience a gradual decline of the condition before entering (7:30 to 08:00 a.m.) in the range of 7-10 times, the condition before the break (8:00 to 9:30 a.m.) in the range of 8 - 12 times and conditions after the break (10:00 to 12:00) in the range of 8-9 times. Based on the data analysis and inter-state conditions in this study were obtained estimate of the tendency toward positive, the tendency of a variable stability (the condition before entering at 07.30.08.00) and stable (the condition before the break at 8:00 to 09:30 and 10:00 to 12:00 at the conditions after the break) , traces of positive data, the level of stability range of the variable (the condition before entering at 07.30.08.00) and stable (the condition before the break at 8:00 to 09:30 and 10:00 to 12:00 at the conditions after the break), changes in the level of positive and 0% overlap of data into three conditions. Thus the hypothesis is accepted, that the game congklak has an effective way to reduce head shaking behavior in autistic children grade 4C in SLB Lubuk Kilangan Padang. It is recommended to teachers can use congklak game to reduce head shaking behavior in children with autism. Keywords: congklak Games; shaking head behavior; children with autism.